A large posterior vaginal wall cyst simulating rectocele: an account of an unusual perplexing case - Garg, Deepali; Marwah, Sheeba; Sharma, Ritu; Salhan, Sudha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Benign cystic lesions of the vagina are uncommon, often being an asymptomatic incidental finding revelled during routine gynaecological examination. Large vaginal wall cysts > 5cm size are a rare gynaecological entity. Most of the work available in literature accounts their mullerian genesis. Large epidermal inclusion cysts are further rarer. Thus, here is described a case illustrating an exceptional case of large epidermal inclusion vaginal wall cyst mimicking rectocele. Also, clinical considerations and relevant literature review on the same has been addressed. A 40 year old lady P2L2 presented in gynecology OPD with complaints of feeling of fullness in the vagina associated with some mass protruding out of the vagina for last few years. Careful evaluation indicated it to be a large posterior vaginal wall cyst 7x6 cm, aping enterocele, lying separate from rectum. The cyst was then surgically excised without any intraoperative or postoperative complications. Giant vaginal cysts are an uncommon occurrence. Meticulous clinical evaluation, bolstered with pertinent investigations can help in clinching the diagnosis early.